Environmental sustainability in the prophetic Sunnah - Abdelaal, Kamal Abdelaal Tamam; Aldhamer, Abdulaziz Abdulrahman; Aljawabrah, Faisal Basim; Abdelqader, Yassin Mahmoud (Edelweiss Applied Science and Technology, 2024)
The purpose of this article is to explore the position of the Prophetic Sunnah on sustaining the green environment, encouraging its preservation, and preventing any tampering or vandalism. The article highlights the Sunnah's emphasis on environmental care by underscoring its instructions regarding the sustainability of natural greenery. This study examines the Prophet’s teachings and directives that urge environmental sustainability by promoting planting and cautioning against actions that harm nature, such as cutting down trees or damaging green spaces. It emphasizes that environmental conservation is an integral yet often overlooked part of the Sunnah. Key findings include that the preservation, enhancement, and careful treatment of the environment and its resources are core values in the Sunnah. The Sunnah explicitly discourages the destruction of trees and green land, even in the most challenging times and conditions, and declares any distortion or damage to the green environment as a transgression in Islamic law. The article concludes with several recommendations, foremost among them being the development of a university-level environmental education program aimed at raising awareness, protecting the environment, and preventing its degradation.